SCHOOL WEB INFORMATION SYSTEM ON STATE VOCATIONAL SCHOOL 1 TIMPEH KAB. DHARMASRAYA - Septia Amrullah; Thomson Mary; Satrio Junaidi (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
SMK Negeri 1 Timpeh is one of the vocational high schools located in Marga Makmur, Timpeh District, Dharmasraya Regency, which was established in 2014. The school is still a new school. So that the school provides information about the school still manually, of course it takes quite a long time. Smk Negeri 1 Timpeh requires the Web as a medium of information to students and the outside community. Based on the existing problems, a web-based information system was built. For school information at SMK Negeri 1 Timpeh. Information system designed with. The SDLC (System Development Life Cycle) method of PHP programming language and MySQL database. So it was built. A web-based school information system at SMK Negeri 1 Timpeh, Dharmasaraya Regency. with the aim of being a medium to promote the SMK 1 TIMPEH school. The outside community and as a media get very efficient information or news about Smk Negeri 1 Timpeh.